Imaging mitochondria through bone in live mice using two-photon fluorescence microscopy with adaptive optics - Zheng, Tianyi; Liversage, Adrian R.; Tehrani, Kayvan F.; Call, Jarrod A.; Kner, Peter A.; Mortensen, Luke J. (Frontiers in Neuroimaging, 2023)
Mitochondria are extremely important organelles in the regulation of bone marrow and brain activity. However, live imaging of these subcellular features with high resolution in scattering tissues like brain or bone has proven challenging. In this work we developed a two-photon fluorescence microscope with adaptive optics (TPFM-AO) for high-resolution imaging, which uses a home-built Shack-Hartmann wavefront sensor (SHWFS) to correct system aberrations and a sensorless approach for correcting low order tissue aberrations. Using AO increases the fluorescence intensity of the point spread function (PSF) and achieves fast imaging of subcellular organelles with 400 nm resolution through 85 µm of highly scattering tissue. We achieved 1.55x, 3.58x and 1.77x intensity increases using AO, and a reduction of the PSF width by 0.83x, 0.74x and 0.9x at the depths of 0, 50m and 85m in living mouse bone marrow respectively, allowing us to characterize mitochondrial health and the survival of functioning cells with a field of view of 67.5 μm x 67.5 μm. We also investigate the role of initial signal and background levels in sample correction quality by varying the laser power and camera exposure time and develop an intensity-based criteria for sample correction. This work demonstrates a promising tool for imaging of mitochondria and other organelles in optically distorting biological environments, which could facilitate the study of a variety of diseases connected to mitochondrial morphology and activity in a range of biological tissues.